MANHAJ HASBI ASH-SHIDIEQI KARYANYA DALAM BIDANG HADIS METODENYA, PEMIKIRANNYA, KRITIK ULAMA SERTA KELEBIHAN DAN KEKURANGANNYA - Adnir, Farid; Syukri, Syukri (UIN Sumatera Utara Medan, 2020)
The purpose of the journal was made so that we could find out about Hasbi Asshiddiqhi's activities. Among Indonesian figures who were considered reformers, who put forward the importance of ijtihad in the early twentieth century. Among them is Hasbi Asshiddiqi from Aceh. Even the latter, including one who directly received education from a modern university founded by Ahmad Surkati, one of the reformers of Islam. In addition, Hasbi Ash-Shiddieqy experienced the forging of renewal with his involvement in two Islamic reform organizations, namely Muhammadiyah and Persis. Activeness in these two Islamic organizations did not necessarily make Hasbi's thinking shackled and limited by the provisions and decisions of the two organizations. For the purposes of discussion, the author will systematize Hasbi's thought in the field of hadith in the following matters. First, his views on the nature of Hadith and Sunnah and their periodization. Second, the criteria for the authenticity of hadith. Third, research and maintenance of Hadith. Fourth, the methodology of understanding hadith (sharh) al-hadîth). Hadith and Sunnah and the Periodization of Hasbi Ash-Shiddieqy Perspectives Regarding the understanding of hadith and sunnah, Hasbi clearly distinguishes between the two terms. Hasbi views that hadith is all events relying on the Prophet, even though the event occurred only once in the Prophet's life, and even though it was only narrated by a narrator. From here we can take the result or essence of his thought, which is very worthy of being said as a reformer in the field of hadith in Indonesia, his courage to oppose the flow or dare to be different from others is a necessity of a Hasbi Asshiddiqi.